Cyanidin-3-O-Glucoside Modulates the In Vitro Inflammatory Crosstalk between Intestinal Epithelial and Endothelial Cells. (8th March 2017) - Ferrari, Daniela; Cimino, Francesco; Fratantonio, Deborah; Molonia, Maria Sofia; Bashllari, Romina; Busà, Rossana; Saija, Antonella; Speciale, Antonio
Abstract : Intestinal epithelium represents a protective physical barrier and actively contributes to the mucosal immune system. Polarized basolateral intestinal secretion of inflammatory mediators, followed by activation of NF- κ B signaling and inflammatory pathways in endothelial cells, efficiently triggers extravasation of neutrophils from the vasculature, therefore contributing to the development and maintenance of intestinal inflammation. Proper regulation of NF- κ B activation at the epithelial interface is crucial for the maintenance of physiological tissue homeostasis. Many papers reported that anthocyanins, a group of compounds belonging to flavonoids, possess anti-inflammatory effects and modulate NF- κ B activity. In this study, by using a coculture in vitro system, we aimed to evaluate the effects of TNF- α -stimulated intestinal cells on endothelial cells activation, as well as the protective effects of cyanidin-3-glucoside (C3G). In this model, TNF- α induced nuclear translocation of NF- κ B and TNF- α and IL-8 gene expression in Caco-2 cells, whereas C3G pretreatment dose-dependently reduced these effects. Furthermore, TNF- α -stimulated Caco-2 cells induced endothelial cells activation with increased E-selectin and VCAM-1 mRNA, leukocyte adhesion, and NF- κ B levels in HUVECs, which were inhibited by C3G. We demonstrated that selective inhibition of the NF- κ B pathway in epithelial cells represents the main mechanism by which C3G exerts these protective effects. Thus, anthocyanins could contribute to the management of chronic gut inflammatory diseases.